Formulation and evaluation of clindamycin HCL in situ gel for vaginal application - Patel, Priya; Patel, Paresh (International Journal of Pharmaceutical Investigation)
Objective: The vagina has been studied as a favorable site for the local and systemic delivery of drugs, for female associated conditions. Vaginal preparations, although generally perceived as safer most still associated with number of problems including multiple days of dosing, dripping, leakage and messiness, causing discomfort to users and expulsion due to the self-cleansing action of the vaginal tract. These limitations lead to poor patient compliance and failure of the desired therapeutic effects. For efficient vaginal delivery of drugs, the delivery system should reside at the site of infection for a prolonged period of time. In situ gel formulation which combines advantages of both gels and solution so that an accurate dose can be administered with ease. These formulations remain in solution state before administration and transforms to gel after administration in to vaginal cavity. Material and Methods: In these formulations we prepared clindamycin loaded hydroxypropyl methycellulose (0.1%) (bioadhesive) and gellan gum (ion activated gelling polymer) based in situ gel system for vaginal application. NaCl (0.9%) was added as an isotonic agent. The developed formulation was characterized for various in vitro parameters such as clarity, refractive index, pH, viscosity, drug release profile, statistical release kinetics, bioadhesive force, and microbial efficacy along with stability studies. To simulate vaginal conditions, synthetic membrane (cellophane hydrated with modified simulated vaginal fluid) was used as model membranes. Results and Discussion: The developed formulation was found to be nonirritant, bioadhesive with good retention properties. Formulations have satisfactory appearance, clarity and drug content in the range 98.1-101%. Refractive index of the gel is ranging from 1.335 to 1.337, proofing the transparency of gel. Furthermore, formulation displayed 33.3% cumulative drug release after 2 h. 67.4% after 6 h and 98.9% after 12 h. Conclusion: Developed formulation should be stable. Hence, formulation is thus a viable alternative to conventional vaginal dosage forms.
Keywords: Clindamycin HCl; gellan gum; hydroxypropyl methycellulose; in situ gel